Applications of synchrotron light to scattering and diffraction in materials and life sciences - Ezquerra, T. A. (Springer, 2009)
"The present set of lecture notes originates from the deeply felt need in the community to bridge the gap between beamline manuals and advanced graduate textbooks. The volume is a collection of tutorials, surveys and reviews. They cover most cases of relevance and interest where the combination of synchrotron light with various scattering and diffraction techniques is a very helpful approach to obtaining essential information about the structure of large molecular assemblies in low-ordered environments. Soft condensed matter and biomaterials, as well as complex fluids, are typical of the materials considered here."
Keywords: záření; rentgenové záření; rentgenová difraktometrie; synchrotrony; difrakce; rozptyl světla; vlastnosti materiálů; struktura materiálů; radiation; X-rays; X-ray diffractometry; synchrotrons; diffraction; light scattering; materials properties; material structure; sborníky; papers of several authors